People's Judgements About Autistic Students' Academic Performance Based on Brief Samples of Their Behaviours - Alhusayni, Afaf (2024)
The number of autistic students attending higher learning institutions is growing, but unfortunately, the majority of them do not complete their studies or are less likely to do so compared to non-autistic individuals (Ashbaugh et al., 2017). They demonstrate an increased incidence of repeating courses or dropping out (Dijkhuis et al., 2020). Studies have revealed that the intellectual demands of college do not pose substantial challenges to autistic students, but they struggle with social relationship and interpersonal competence issues, anxiety, stress, poor emotional regulation and difficulties in executive functioning (Brede et al., 2017; Dijkhuis et al., 2020). Therefore, it is critical to examine how communication and socialisation difficulties affect their academic life. In this series of studies, we investigated neurotypical perceptions about autistic university students' academic performance. In Study 1, we developed an experimental paradigm by recording brief samples of the participants' autistic and non-autistic target behaviours while they were writing about different life experiences. These videos were then shown to a group of nonautistic perceivers, who made judgements about the autistic students' academic life (success, motivation, happiness and grade). The findings suggest that autistic targets are judged more negatively in all academic aspects compared to non-autistic targets. In Study 2, we replicated these findings in a new target group and assessed the veracity of these negative judgements by comparing perceiver judgements to target self-reports. Autistic students faced more negative judgements in all aspects of academic life compared to non-autistic targets. Their motivation and happiness were underestimated, while non-autistic students were accurately perceived. However, both groups were unaware of how they were perceived, believing that they would receive more positive judgements. In Study 3, we examined how different social contexts under high-demand (social interaction and self-presentation) and low demand conditions (writing) could affect autistic individuals' judgements of academic success. We recorded three types of video recordings featuring both autistic and non-autistic individuals. The targets were filmed while either filling out a questionnaire and interacting with the experimenter or introducing themselves to the camera after being informed about the study's objectives to determine whether such disclosures would influence the perceptions formed about them. The findings show that negative peer judgements persist in different social contexts and do not change based on the situations.